DEVELOPMENT OF COOPERATIVE LEARNING MODELS WITH THE "TIME TOKEN" TO INFLUENCE ON THE ENGLISH SPEAKING ABILITY OF WASHLIYANI HIGH SCHOOL STUDENTS - Aulia, Shabrina; Harianto, Harianto; Hasibuan, Ahmad Laut; Tambusai, Azhary; Asnawi, Asnawi (PROJECT (Professional Journal of English Education), 2024)
The research objective was to know the effectiveness of the cooperative learning model with time token method on the English language proficiency of Washliyani Middle School students compared to previous teaching methods. This research was quantitative with experimental research design. In this research, the writer uses a quantitative data analysis technique. The quantitative data of this research was analyzed by using statistical method. According to the result of the research of the Wilcoxon test conducted by the researchers, it was found that the significance values for the control and treatment groups were 0.002 and 0.000, respectively. These values were lower than the α value of 0.05, indicating that both teaching methods employed in the control and treatment class had a significant impact on improving students' speaking ability. N-Gain Effectiveness Index indicated that the time token method demonstrated a 63.56% effectiveness rate in improving students' speaking ability. This categorization falls under the range considered "moderately effective" for enhancing students' speaking skills.